Relationship between children with neurodevelopmental disorders and their caregivers and friends during early phase of COVID-19 school closure in Japan: Association with difficulty in implementing infection prevention measures - Tomoka Yamamoto; Sanae Tanaka; Arika Yoshizaki; Yuko Yoshimura; Aishah Ahmad Fauzi; Aida Syarinaz; Ahmad Adlan; Subhashini Jayanath; Norhamizan Hamzah; Haruo Fujino; Masaya Tachibana (BMC, 2022)
Abstract Background Due to the COVID-19 pandemic people had to implement various infection prevention measures. Researchers have reported the difficulties experienced by children with neurodevelopmental disorders in implementing these measures and their caregivers' resultant anxiety and stress. This study examined the relationship between these difficulties and the deterioration of the children's relationships with their caregivers and friends during school closure and after school reopened. Methods A total of 150 caregivers of children with neurodevelopmental disorders answered a questionnaire asking about parent‒child relationships, their child's friendships, and the presence or absence of difficulty in implementing infection prevention measures at three time points: before the pandemic, while schools were closed, and after school reopened. The frequency and percentages of the child's behavioral problems, deterioration in their relationships, and difficulty implementing infection control measures were calculated. Using the relationship deterioration scores, independent and multiple regression analyses were performed for the presence or absence of difficulty implementing infection control measures, presence or absence of caregivers' mental health concerns, and the presence or absence of deterioration of one or more problematic behaviors. Results Overall, 84.1% of the children displayed difficulties implementing infection prevention measures. No relationship was observed between difficulty with infection prevention measures and deterioration in their relationships with parents and friends when schools were closed. After school reopened, however, deterioration in parent‒child relationships correlated positively with difficulty in hand-washing, and deterioration of friendships correlated positively with the maintenance of social distancing and difficulty in hand-washing. Deterioration of friendships correlated negatively with difficulty in voluntarily complying with stay-at-home requests. Conclusion Difficulty in implementing infection prevention measures was related to deterioration in social relationships with parents and friends of children with neurodevelopmental disorders during the school reopening period, following COVID-19 school closure in Japan. Under a condition requiring heightened infection control, close monitoring may be necessary for the social relationships in children with neurodevelopmental disorders.